The wax pack : on the open road in search of baseball's afterlife - Balukjian, Brad (University of Nebraska Press, 2020)
""The Wax Pack," part baseball nostalgia and part road trip travelogue, follows Brad Balukjian as he tracks down players from a single pack of baseball cards from 1986"--